Cybereducation: A Quiet Revolution in Cyberspace. On the Need for Cyberpedagogy - Biernat, Tomasz (Paedagogia Christiana, 2023)
As a result of a quiet revolution in the last two decades, a new form of education has emerged. Cybereducation is the effect of the rapid advancement in information technology and the emergence of cyberspace as a new environment for human activity and education. The cyberenvironment creates a hypertextual educational reality that is hardly transparent and has a specific impact. Cybereducation is different than education in the real environment. Both types of educational interactions – analogue and digital – interact with each other, leading to a modification of the upbringing process. The emergence of the educational cybersecurity and cybereducation is a great challenge for the existing pedagogical knowledge and practice. An important issue in this context is the problem of educational cybersecurity and prevention of cyberbullying. The analyses presented in the article may serve as an argument to recognize cyberpedagogy as a new trend in education sciences.